Lung Isolation in the Patient With a Difficult Airway. (June 2018) - Collins, Stephen R.; Titus, Brian J.; Campos, Javier H.; Blank, Randal S.
Abstract : One-lung ventilation is routinely used to facilitate exposure for thoracic surgical procedures and can be achieved via several lung isolation techniques. The optimal method for lung isolation depends on a number of factors that include (1) the indication for lung isolation, (2) anatomic features of the upper and lower airway, (3) availability of equipment and devices, and (4) the anesthesiologist's proficiency and preferences. Though double-lumen endobronchial tubes (DLTs) are most commonly utilized to achieve lung isolation, the use of endobronchial blockers offer advantages in patients with challenging airway anatomy. Anesthesiologists should be familiar with existing alternatives to the DLT for lung isolation and alternative techniques for DLT placement in the patient with a difficult airway. Newer technologies such as videolaryngoscopy with or without adjunctive fiberoptic bronchoscopy may facilitate intubation and lung isolation in difficult airway management.